Snacks, farinha pré-gelatinizada e massa alimentícia elaborados com grãos de milheto [Pennisetum glaucum (L.) R. Br.] e gritz de milho (Zea mays) - Oliveira, Déborah Patrícia Leal (2013)
Pearl millet is a rich nutritionally cereal, being a major source of protein countries of the semiarid region of the African continent. The pearl millet crops are in expansion on Brazilian Savanna due the plant characteristics that are compatible to the climate and soil of the region. However, in Brazil, the grains of millet are not widely used in food, it was noted with advantageous insertion of this cereal in the diet of the population as this has major advantages over other commonly used cereals as the lowest price, the more quantity and better quality of fiber lipid and protein. The thermoplastic extrusion was used for the preparation of products with the millet that was mixed with corn grits because it presents favorable characteristics for processing used. This study was conducted in order to develop and evaluate the nutritional quality, technological and sensory snacks, pre-gelatinized flour (FPG) and pasta-based mixture of millet [Pennisetum glaucum (L.) R. Br] and gritz of corn (Zea mays L.). For extruding the mixture of grains of millet and corn gritz was used rotational central composite design for the best moisture conditions of the raw material and temperature of the extruder zone 3. The snacks were optimized according to the expandability and pregelatinized flour according to the absorption capacity and water solubility. After optimization of flour, which showed better gelatinization was applied in the preparation of pasta. This was prepared using the mixture design with ternary composition (extruded flour, corn flour and millet raw) to find what proportion of ingredients that got the best features of cooking pasta. Snacks with 11% moisture content of the raw material and 90 ° C temperature were those with greater expansion and were the most desirable second test of desirability. When they were being flavored sensory acceptance and its nutritional composition were classified as high fiber content. The pre-gelatinized flour with highest absorption capacity and water solubility was the one with the same extrusion conditions optimized snack. The proportion of ingredients of the mass had the best cooking conditions was 10% pre-gelatinized flour, 25% corn and 65% of pearl millet flour. The pasta was accepted for flavor, texture and appearance of the panelists. However, it was possible to extrude grains of millet and corn gritz and also the development of products with good nutritional and sensory characteristics.